Prescription of antibiotics for respiratory tract infections in mainland Portugal - Caldeira, Luis (2004)
The authors present the results from a prospective study aimed at the characterization and evaluation of the adequateness of the prescription of antimicrobials for systemic use in respiratory infections in primary care. For the purposes of the study, ten similar questionnaires concerning the type of antibiotic which was prescribed for respiratory tract infections were submitted to a sample of general practitioners (GP), randomized by successive staging, at the national level, between December 2001 and January 2002. Two hundred forty seven GP have participated in the study by sending back, at least, one adequately filled questionnaire. A total of 2200 prescriptions were evaluated, corresponding to 2257 therapeutic indications. Mean patients age was 31.87 years. The indications leading to antibiotic prescription in those with 100 or more validated questionnaires were tonsillitis (663, 29.38%), bronchitis (430, 19.05%), otitis (315, 13.96%), sinusitis (232, 10.28%), pharyngitis (228, 10.10%), rhinitis/rhinopharyngitis (212, 9.39%) and pneumonia (116, 5.14%). The most frequently prescribed antimicrobials at the ATC3 level were betalactam/penicillins (50.55%), macrolides (23.09%), cephalosporins (14.77%), quinolones (8.32%), tetracyclines (2.45% and sulphonamides/trimethoprim (0.59%). At the ATC5 level, the most frequently prescribed antimicrobial was amoxycillin/clavulanic acid (35.36%), which was also the most frequently prescribed antibiotic for each individual indication. As far as the choice for the antibiotic for each indication is concerned, some inadequacies were detected, namely regarding the large and unjustified use of amoxycillin/clavulanic acid for the treatment of tonsillitis. Also, antimicrobials were frequently prescribed for situations for which they are not currently formally indicated, and the recommendations of the European Drug Formulary regarding first-line treatment for the concerned indications were not observed, with the exception of pneumonia. The authors conclude that significant clinical and economic benefit may be obtained by improving current clinical practice through appropriate interventions.